157k views
3 votes
How do I factor x^4-5x^2+6?

1 Answer

3 votes

Answer:


=(x^2-3)(x^2-2)

Explanation:

So we have the expression:


x^4-5x^2+6

And we wish to factor it.

First, let's make a substitution. Let's let u be equal to x². Therefore, our expression is now:


=u^2-5u+6

This is a technique called quadratic u-substitution. Now, we can factor in this form.

We can use the numbers -3 and -2. So:


=u^2-2u-3u+6

For the first two terms, factor out a u.

For the last two terms, factor out a -3. So:


=u(u-2)-3(u-2)

Grouping:


=(u-3)(u-2)

Now, substitute back the x² for u:


=(x^2-3)(x^2-2)

And this is the simplest form.

And we're done!

User Totic
by
5.4k points